Bioaktivitas Turunan Metil Sinamat Terhadap Pertumbuhan Bakteri Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aureugenosa dan Jamur Candida albicans - Teni Ernawati; Andri Budiana (Syarif Hidayatullah State Islamic University, 2015)
Methyl cinnamic is a compound isolated from Alpinia malaccensis included in the family Zingiberaceae. A. malaccensis in Indonesia known as galangal forest. Some studies inform that ginger has anti-bacterial and pharmacologically galangal act as an antifungal. In this study the bioactivity of the compound methyl cinnamate and methyl cinnamic derivative which results cinnamic methyl esterification compound on the growth of Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Pseudomonas aureugenosa and fungus Candida albicans. Methyl cinnamic derivative compounds tested are; cinnamic acid, cinnamic ethyl, butyl and 2-butyl cinnamic cinnamic. Anti-microbial test results showed that of the samples tested, cinnamic acid is able to inhibit microbial growth of S. aureus, B. subtilis, E. coli and P. aureugenosa and fungi C.albicans.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3176